Polycyclic aromatic compounds (PACs) in ambient air of Svalbard : concentrations, seasonal trends, sources, and transformation processes - Drotikova, Tatiana (Norwegian University of Life Sciences, Ås, 2021)
Polycyclic aromatic compounds (PACs) are ubiquitous organic, gaseous, and particulate chemicals primarily emitted from incomplete combustion of fossil fuels, waste, and open biomass burning, including wildfires. Several PACs are classified as known, probable or possible carcinogens and toxicants. Atmospheric transport is the most efficient way for PACs’ global distribution. Due to a tendency to increase in environmental compartments and biota and low degradation rates in polar conditions, PACs have been identified as chemicals of emerging Arctic concern. Polysykliske aromatiske komponenter (PAC) er organiske, flyktige og partikulært bundne kjemikalier som primært slippes ut fra ufullstending forbrenning av fossilt brensel, avfall og åpen biomassebrenning inkludert skogbranner. Mange PAC-er er klassifiserte som, sannsynlige og/eller potensiellt kreftfremkallende forbindelser og toksiske. Atmosfærisk transport er den mest effektive måten for global transport og fordeling av PAC-er. Grunnet disse komponentenes evne til opphoping i miljøet, i tillegg til lang tilstedeværelse i biota på grunn av dens lave nedbrytningshastighet, har PAC blitt identifisert som prioriterte forurensninger i Arktis. UNIS